What’s Old is New Again: How State Attorneys General Can Reinvigorate UDAP Enforcement to Combat Crisis Pregnancy Center Deception - Vlach, Kate (Columbia Journal of Gender and Law, 2020)
For decades, abortion opponents have set up thousands of crisis pregnancy centers (CPCs) across the country to dissuade women from terminating their pregnancies. Although some CPCs make their anti-abortion stance clear, others rely on deception as part of their operational model. Many CPCs advertise as abortion clinics and then lie to unwitting consumers about whether they are pregnant and how quickly they should seek medical assistance. As a result, some women who mistakenly visit CPCs are delayed in obtaining abortion services for so long that they forfeit the right to abortion altogether. Cities and states attempting to rein in this deception over the last decade have enacted laws requiring CPCs to disclose the true nature of their services. But in 2018, the Supreme Court declared such CPC disclosure laws unconstitutional, leaving advocates in search of an alternate solution. This Article sketches a roadmap for state governments wishing to respond to CPC fraud in the wake of this new constitutional constraint. It retraces a largely forgotten strategy of using Unfair, Abusive, and Deceptive Practices Acts (UDAP laws) to investigate and enjoin CPCs’ harmful practices and explores the opportunities and challenges presented by adapting UDAP laws to the modern CPC problem. Seizing on the rising importance of state attorneys general as national policymakers, this Article lays out a pragmatic path forward for curbing CPC deception that interferes with women’s reproductive decisionmaking autonomy.